High-reflection adhesive as well as preparation method and application thereof
By forming a reflective glue with a silicone reflective coating on the wall of the LED cup cavity, the performance degradation caused by the agglomeration of inorganic nanoparticles and excessive use in the prior art is solved, and efficient improvement of LED light output efficiency and enhanced film stability is achieved.
Patent Information
- Application Number
- CN202311263252.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art improves the light output efficiency by adding inorganic nanoparticles with high refractive index to the LED packaging glue, but due to the agglomeration of nanoparticles and the degradation of performance caused by excessive use, it cannot effectively meet the needs of high-brightness and high-light efficiency LEDs.
A reflective glue is provided, which consists of component A and component B, which includes phenyl vinyl silicone resin, catalyst and vinyl silicone oil, and component B includes hydrogen-containing silicone oil and titanium dioxide. By forming a silicone reflective coating on the wall of the LED cup cavity, diffuse reflection and improve light output efficiency.
By breaking the bottleneck of improving luminous efficiency in the refractive index of the prior art, the light output efficiency of LED devices is significantly improved, and the components are simple and controllable, and the preparation process is simple, which enhances the stability and adhesion of the adhesive film, reduces air thermal resistance, improves heat dissipation ability, and extends the service life of the device.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to a high-reflective adhesive and a preparation method and application thereof. Technical Background
[0002] LED is considered to be a promising new lighting source in the 21st century. As the fourth generation of light source after incandescent lamps, fluorescent lamps and high-intensity discharge lamps, LED has a very bright development prospect. It has the characteristics of low power consumption, long life, small size, low heat generation, strong and durable. It has been widely used, such as traffic lights, display lights and large-screen displays.
[0003] However, with the rapid development of the LED industry, the power and brightness of LED products are increasing day by day, and how to improve the luminous efficiency of LEDs has become a research focus. At present, the light extraction efficiency is generally improved by increasing the refractive index of LED encapsulation glue. Usually, inorganic nanoparticles with high refractive index are added to the encapsulation colloid, such as adding nanoparticles such as zirconium dioxide, aluminum oxide, and titanium dioxide to the encapsulation glue of LED light-emitting devices to increase the refractive index of the encapsulation glue, increase the light extraction rate of the device, and achieve the effect of energy saving and emission reduction. However, it is worth noting that due to the small size of inorganic nanoparticles with high refractive efficiency, nano zirconium oxide particles are easy to agglomerate in the organic matrix. The agglomeration phenomenon causes local particles to be too large and unevenly dispersed, thereby greatly reducing the transmittance of the composite matrix, which in turn reduces the light extraction performance of the LED device. Therefore, inorganic nanoparticles need to be surface modified before adding and using; and because the functions of inorganic nanoparticles are relatively single, when the amount of inorganic nanoparticles is too large, although it can meet the requirements of high refractive index, other properties of the encapsulation material, such as mechanical properties, thermal stability, weather resistance, and electrical insulation performance, are affected to a certain extent and reduced. It can be seen that the method of increasing the refractive index of the package to improve the light extraction efficiency of LED by inorganic nanoparticles still has certain limitations. Therefore, a resin composition that can effectively improve the light extraction efficiency is needed to meet the needs of high-brightness and high-efficiency LEDs. Summary of the invention
[0004] To solve the above technical problems, the present invention provides a reflective adhesive, component A: 40-130 parts of phenyl vinyl silicone resin, 1-25 parts of catalyst, 10-50 parts of vinyl silicone oil, component B: 1-10 parts of hydrogenated silicone oil, 10-40 parts of titanium dioxide; the titanium dioxide particle size is 0.1μm-0.5μm.
[0005] Preferably, the component A further comprises 1-10 parts by weight of a silane coupling agent, the general formula of which is Si(OC n H 2n+1 ) a(R 1 ) b (R 2 ) c , R 1 Selected from C 1 -C 10 Alkyl, C 1 -C 10 The alkoxy group, R 2 Selected from C having a terminal substituted by at least one of a hydroxyl group, an ethylenically unsaturated functional group or an epoxy functional group 1 -C 8 an alkyl ether group or an N-heteroalkyl group; a+b+c = 4, a, b, c are integers of 0-3 and are not 0 at the same time, c≥1; and n is an integer of 1-10.
[0006] Furthermore, the silane coupling agent is selected from a hydroxyl-terminated silane coupling agent, a vinyl-terminated silane coupling agent or an epoxy-terminated silane coupling agent.
[0007] Further, the silane coupling agent is selected from vinyl trichlorosilane, vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(2-methoxyethoxy)silane, vinyl triacetoxysilane, vinyl triperoxide tert-butylsilane, vinyl methyl dichlorosilane, glycidyl trimethoxysilane, y-glycidyl ether oxypropyl trimethoxysilane, 3-glycidyl ether oxypropyl triethoxysilane, 3-(2,3-glycidyloxy)propyl trimethoxysilane, 3-glycidyl ether oxypropyl methyl diethoxysilane, 3-[(2,3)-glycidyloxy]propyl methyl dimethoxysilane, 3-glycidyl ether oxypropyl dimethylmethoxysilane, (3-glycidyloxypropyl) dimethylethoxysilane, 3-[bis(2-hydroxyethyl)amino]propane triethoxysilane.
[0008] Preferably, the B component further comprises 0.1-5 parts by weight of a tackifier, wherein the tackifier is selected from polysiloxanes having silicon-boron bonds in the main molecular chain, and the polysiloxanes further contain any one or more of alkyl, phenyl, vinyl, epoxy, hydroxyl and amino groups.
[0009] Furthermore, the tackifier described in the present invention is selected from the silicon-boron modified tackifiers of model Z-1501, Z-1504 or Z-1506 produced by Jiangxi Nan New Materials Co., Ltd.
[0010] Preferably, the vinyl content of the phenyl vinyl silicone resin is 1-3 mmol / g, the hydrogen content of the hydrogen-containing silicone oil is 1-20 mmol / g, and the vinyl content of the vinyl silicone oil is 5-15 mmol / g.
[0011] Preferably, the invention further comprises 50-80 parts by weight of phenyl hydrogenated silicone resin, with a hydrogen content of 0.1-1 mmol / g.
[0012] Preferably, the catalyst is selected from a platinum catalyst, and the platinum catalyst is one or more combinations of a platinum catalyst coordinated with tetrahydrofuran, a platinum catalyst coordinated with vinyl siloxane, a platinum catalyst coordinated with methyl vinyl siloxane, a platinum catalyst coordinated with isopropanol, a platinum catalyst coordinated with diethyl phthalate and a platinum catalyst coordinated with aminohydroxy polysiloxane.
[0013] Preferably, the present invention further comprises 0.1-1 parts by weight of an inhibitor, wherein the inhibitor is one or more combinations of ethynyl cyclohexanol, silylated acetylenic alcohol, methyl butynol, propyl acetylenic alcohol, dimethyl acetylenic alcohol, diethyl maleate and 2-vinyl isopentanol.
[0014] In a second aspect, the reflective adhesive is applied to the LED cup cavity wall.
[0015] In a third aspect, the present invention provides a method for preparing a reflective adhesive, comprising the following steps: S1: Preparation of component A: Phenyl vinyl silicone resin, vinyl silicone oil, platinum catalyst and silane coupling agent are put into a reaction kettle, the temperature is controlled between 25°C and 50°C, stirred for 3-5h, and vacuumed to obtain component A; S2: Preparation of component B: Phenyl hydrogenated silicone resin, hydrogenated silicone oil, inorganic filler, inhibitor and adhesion promoter are put into a reaction kettle, the temperature is controlled between 25°C and 50°C, stirred for 3-5h, and vacuumed to obtain component B.
[0016] As the vinyl content decreases, the fewer crosslinking points are generated in the composition, making it more difficult to form a high-density three-dimensional network structure, resulting in poor mechanical properties of the final cured product. As the vinyl content increases, the molecular weight of the vinyl silicone oil increases, and its molecular weight distribution is also relatively wide, which easily leads to an increase in the viscosity of the vinyl silicone oil, and its fluidity becomes worse, which is not conducive to curing and use. By regulating the content of the vinyl and hydrogen-containing components, the resulting cured composition has good optical and mechanical properties.
[0017] Compared with the prior art, the reflective adhesive provided by the present invention has the following beneficial effects: 1. In order to improve the light extraction efficiency of LED devices, the refractive index of the packaging material is generally increased. The present invention provides a reflective adhesive applied to the wall of the LED cup cavity, which forms a layer of organic silicon reflective coating on the wall of the cup cavity to reduce the diffuse reflection of the LED light on the wall of the cup cavity, breaking the technical bottleneck of the prior art of improving the luminous efficiency by the refractive index, further improving the light extraction efficiency of the LED device, with simple and controllable components and simple preparation process; 2. The amount of A and B adhesive components is increased to 1: (4-10), breaking the ratio limit of 1: (1-2) in the prior art. By adjusting the amount of components and introducing small molecule silane coupling agents, the effect of the self-coupling of the residual vinyl and active hydrogen on the stability of the adhesive film due to the restricted molecular motion in the late stage of colloid curing is solved. The reflective adhesive has the advantages of high adhesion to the substrate, especially the bracket substrate, and high reflectivity and luminous efficiency, which reduces the air thermal resistance, improves the heat dissipation capacity of the LED device, and thus prolongs the service life of the device. 3. The reflective adhesive provided by the present invention is divided into two components, A and B, which are mixed before use to avoid turbidity and other phenomena that affect the optical properties during storage or transportation of the mixed components; titanium dioxide and the catalyst are separated, and titanium dioxide and hydrogen-containing silicone oil are located in the same component. The hydrogen-containing silicone oil coats the surface of titanium dioxide to improve the dispersibility of titanium dioxide, while avoiding the phenomenon of catalyst poisoning caused by the reaction of titanium dioxide and catalyst, thereby obtaining an adhesive material with good optical and mechanical properties. Implementation
[0018] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially. Example 1
[0019] Component A includes 30 parts of phenyl vinyl silicone resin, 10 parts of vinyl silicone oil, 1 part of Custer catalyst, and 1 part of 3-[bis(2-hydroxyethyl)amino]propanetriethoxysilane; component B includes 50 parts of phenyl hydrogenated silicone resin, 1 part of hydrogenated silicone oil, 10 parts of 0.6 μm alumina surface modified titanium dioxide powder, 0.1 part of ethynyl cyclohexanol, and 0.1 part of Z-1501 viscosity enhancer.
[0020] Preparation: S1: Phenyl vinyl silicone resin, vinyl silicone oil, Custer catalyst and 3-[bis(2-hydroxyethyl)amino]propanetriethoxysilane are placed in a reaction kettle and stirred at 40°C and 1500 rpm for 4 hours, and then vacuumed to 0.1 MPa for 30 minutes to remove volatile substances to obtain component A; S2: Phenyl hydrogen silicone resin, hydrogen silicone oil, modified titanium dioxide, ethynyl cyclohexanol and tackifier b1 are placed in a reaction kettle and stirred. The temperature is controlled at 40°C and the stirring speed is 1500 rpm for 4 hours. Then, the volatile substances are removed at a vacuum degree of 0.1 MPa and a temperature of 40°C for 30 minutes to obtain component B. Embodiment 2-13:
[0021] The reflective adhesives of Examples 2-8 were prepared according to the ingredients and contents shown in Table 1 below, and the operating steps were the same as those of Example 1.
[0022] Table 1
[0023] Silane coupling agent a1 is 3-glycidoxypropyltriethoxysilane, silane coupling agent a2 is vinyltriethoxysilane, silane coupling agent a3 is glycidoxypropyl terminated polydimethylsiloxane, silane coupling agent a4 is hydroxy terminated polydimethylsiloxane, and silane coupling agent a5 is butyltriethoxysilane. Embodiment 14:
[0024] Component A includes 40 parts of phenyl vinyl silicone resin, 10 parts of vinyl silicone oil, 1 part of Custer catalyst, 1 part of 3-[bis(2-hydroxyethyl)amino]propanetriethoxysilane, and 10 parts of 0.6μm alumina surface-modified titanium dioxide powder; component B includes 50 parts of phenyl hydrogenated silicone resin, 1 part of hydrogenated silicone oil, 0.1 part of ethynyl cyclohexanol, and 0.1 part of Z-1501 viscosity enhancer.
[0025] The preparation method is the same as that in Example 1.
[0026] The curing compositions obtained in Examples 1-14 are numbered 1-14 respectively. Component A and component B obtained in Nos. 1-14 are mixed and stirred respectively, and then injection molded into a mold, with a vacuum degree of 0.1 MPa, a temperature of 20°C, and a vacuum time of 30 min. The test samples are prepared by curing reaction at 150°C for 40 min, and the hardness is tested by a Shore D hardness tester, the shear strength is tested by a shear tester, and the initial reflectivity value of the sample is measured by a reflection spectrometer. The sample is then placed at 150°C for aging for 500 hours, and then the reflectivity value is tested. The test results are shown in Table 2 below: Table 2
[0027] As can be seen from the above table, compared with Examples 1-8, as the weight fraction of component B increases, the shear strength and thermal stability of the reflective adhesive are continuously improved. Compared with Examples 8-10, the increase of the hydrogen-containing component makes the obtained reflective adhesive have better hardness, but the shear strength is significantly reduced. It can be seen from the setting of adding silane coupling agents in Examples 11-13 that the silane coupling agents or macromolecular silane coupling agents that do not contain reactive groups such as hydroxyl, epoxy and vinyl groups have little effect on the shear strength of the reflective adhesive. The present invention effectively improves the shear strength and curing depth of the reflective adhesive by regulating the ratio of components A and B and adding a small molecule silane coupling agent, and has good thermal stability and reflection efficiency while increasing the bonding force between the reflective adhesive and the substrate surface.
[0028] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A highly reflective adhesive, characterized in that: The invention comprises the following components in parts by weight: component A: 40-130 parts of phenyl vinyl silicone resin, 1-25 parts of catalyst, and 10-50 parts of vinyl silicone oil; component B: 1-10 parts of hydrogen-containing silicone oil and 10-40 parts of titanium dioxide; the particle size of the titanium dioxide is 0.1 μm-0.5 μm.
2. The high reflective adhesive according to claim 1, characterized in that: The component A further comprises 1-10 parts by weight of a silane coupling agent, the general formula of which is Si (OC n H 2n+1 ) a (R1) b (R2) c , R1 is selected from C1-C 10 Alkyl, C1-C 10 an alkoxy group, R2 is selected from a C1-C8 alkyl ether group or an N-heteroalkyl group substituted at the terminal with at least one of a hydroxyl group, an ethylenically unsaturated functional group or an epoxy functional group; a+b+c=4, a, b, c are integers of 0-3 and are not 0 at the same time, c≥1; and n is an integer of 1-10.
3. The high reflective adhesive according to claim 1, characterized in that: The B component further comprises 0.1-5 parts by weight of a tackifier, and the tackifier is selected from polysiloxanes containing silicon-boron bonds in the main molecular chain.
4. The high reflective adhesive according to claim 1, characterized in that: The phenyl vinyl silicone resin has a vinyl content of 1-3 mmol / g, the hydrogen content of the hydrogen-containing silicone oil is 1-20 mmol / g, and the vinyl content of the vinyl silicone oil is 5-15 mmol / g.
5. The high reflective adhesive according to claim 1, characterized in that: The B component also includes 50-80 parts by weight of phenyl hydrogen-containing silicone resin, with a hydrogen content of 0.1-1 mmol / g.
6. The high reflective adhesive according to claim 1, characterized in that: The titanium dioxide surface is treated and modified by an aluminum coating method or a silicon coating method.
7. The high reflective adhesive according to claim 1, characterized in that: The catalyst is selected from a platinum catalyst, and the platinum catalyst is one or more combinations of a platinum catalyst coordinated by tetrahydrofuran, a platinum catalyst coordinated by vinyl siloxane, a platinum catalyst coordinated by methyl vinyl siloxane, a platinum catalyst coordinated by isopropanol, a platinum catalyst coordinated by diethyl phthalate, and a platinum catalyst coordinated by aminohydroxy polysiloxane.
8. The high reflective adhesive according to claim 1, characterized in that: The B component further comprises 0.1-1 parts by weight of an inhibitor, which is one or more combinations of ethynyl cyclohexanol, silylated acetylenic alcohol, methyl butynol, propyl acetylenic alcohol, dimethyl acetylenic alcohol, diethyl maleate and 2-vinyl isopentanol.
9. The high reflective adhesive according to any one of claims 1 to 8 is applied to the wall of an LED cup cavity.
10. A method for preparing a highly reflective adhesive, characterized in that: The steps include: S1: Preparation of component A: Phenyl vinyl silicone resin, vinyl silicone oil, platinum catalyst and silane coupling agent are put into a reaction kettle, the temperature is controlled between 25°C and 50°C, stirred for 3-5h, and vacuumed to obtain component A; S2: Preparation of component B: Phenyl hydrogenated silicone resin, hydrogenated silicone oil, inorganic filler, inhibitor and adhesion promoter are put into a reaction kettle, the temperature is controlled between 25°C and 50°C, stirred for 3-5h, and vacuumed to obtain component B.